2020
DOI: 10.1073/pnas.2004656117
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionarily diverse LIM domain-containing proteins bind stressed actin filaments through a conserved mechanism

Abstract: The actin cytoskeleton assembles into diverse load-bearing networks, including stress fibers (SFs), muscle sarcomeres, and the cytokinetic ring to both generate and sense mechanical forces. The LIM (Lin11, Isl- 1, and Mec-3) domain family is functionally diverse, but most members can associate with the actin cytoskeleton with apparent force sensitivity. Zyxin rapidly localizes via its LIM domains to failing SFs in cells, known as strain sites, to initiate SF repair and maintain mechanical homeostasis. The mech… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
79
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(101 citation statements)
references
References 53 publications
4
79
0
2
Order By: Relevance
“…Rap1 and its GEF Dzy are required for proper anisotropic apical constriction and ventral furrowing, and these factors may regulate these junctional rearrangements ( Sawyer et al, 2009 ; Spahn et al, 2012 ). Ventral junctions also recruit the tension-sensitive protein Ajuba ( Winkelman et al, 2020 ; Sun et al, 2020 ; Rauskolb et al, 2019 ). These results indicate that ventral cells undergo a number of changes that might alter their response to ectopic Rho1 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Rap1 and its GEF Dzy are required for proper anisotropic apical constriction and ventral furrowing, and these factors may regulate these junctional rearrangements ( Sawyer et al, 2009 ; Spahn et al, 2012 ). Ventral junctions also recruit the tension-sensitive protein Ajuba ( Winkelman et al, 2020 ; Sun et al, 2020 ; Rauskolb et al, 2019 ). These results indicate that ventral cells undergo a number of changes that might alter their response to ectopic Rho1 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, it has become more apparent that the mechanical state of filamentous actin (tension, curvature, torsion) affects the binding and activity of many actin-binding proteins (Jégou and Romet-Lemonne, 2021;Zimmermann et al, 2017). Recent work (Sun et al, 2020;Winkelman et al, 2020) has highlighted that a conserved mechanism in LIM domains confers mechanosensitivity to proteins from the FHL, zyxin and paxillin families among others to sense strained actin filaments. The LDP testin appears unique in that the FL protein resides primarily in the cytoplasm, while its N-terminal half recognizes unstrained actin filaments and its C-terminal half recognizes strained actin filaments (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…2) to recognize SFSSs. Previous research has suggested that multiple LIM domains are required for mechanosensitivity(Sun et al, 2020;Winkelman et al, 2020). Surprisingly, not only did each individual LIM domain of testin display FA localization (Figs.…”
mentioning
confidence: 82%
“…The pre-LIM region of Ajuba binds the Cas CCH/FAT tightly and Cas is mis-localized in ajuba-deficient cells (Pratt et al, 2005). The ajuba LIM domains bind to actin filaments under tension (Winkelman et al, 2020) and localize to adhesions (Pratt et al, 2005). Thus, ajuba or other LIM domain proteins, rather than BCAR3, may be responsible for localizing Cas to adhesions.…”
Section: Discussionmentioning
confidence: 99%
“…Zyxin binds the Cas homolog NEDD9 (Yi et al, 2002) but zyxin appears in adhesions after Cas (Zaidel-Bar et al, 2004), so is unlikely to be responsible for Cas localization. Ajuba contains a pre-LIM region that binds tightly to the Cas CCH/FATand a LIM region that binds to actin filaments under tension and localize to adhesions (Pratt et al, 2005, Winkelman et al, 2020). Moreover, Cas is mis-localized in ajuba-deficient cells (Pratt et al, 2005).…”
Section: Discussionmentioning
confidence: 99%